(untitled) - Paulo Cesar Modesto; Fernando Campos Gomes Pinto (Arquivos de Neuro-Psiquiatria)
Objective:To compare the functional electrical stimulation associated with functional kinesiotherapy alone in patients after ischemic cerebrovascular accident.Methods:The study included 20 patients who were divided into two groups: Group I (GI): functional electrical stimulation plus functional kinesiotherapy and Group II (GII): functional kinesiotherapy. We evaluated active and passive range of motion, in knee flexion and extension muscle strength, activities of daily living and quality of life. The evaluations were conducted in the pretreatment period, after 10 sessions and after 20 physical therapy sessions.Results:There was a significant improvement in all variables studied for both groups. However, significant improvements for the sub-items functional capacity and social aspects were seen only in the patients treated with associated functional electrical stimulation and kinesiotherapy.Conclusion:Although both groups of patients improved with the treatment, the association of functional electrical stimulation and kinesiotherapy showed superiority in two quality of life items, in the sub-items functional capacity and social aspects. Objetivo:Comparar a estimulação elétrica funcional associada à cinesioterapia com a cinesioterapia funcional isolada no membro inferior de pacientes em fase subaguda após acidente vascular cerebral isquêmico.Método:Participaram do estudo 20 pacientes divididos em 2 grupos: Grupo I (GI): eletroestimulação funcional mais cinesioterapia funcional e Grupo II (GII): cinesioterapia funcional. Foram avaliadas as amplitudes de movimento ativo e de movimento passivo em flexão e extensão do joelho, a força muscular, as atividades da vida diária e a qualidade de vida. As avaliaçães foram realizadas nos períodos pré-tratamento, após 10 e após 20 sessões de fisioterapia.Resultados:Houve melhora significativa em todas as variáveis estudadas para ambos os grupos. Contudo, melhorias significativas para os subitens capacidade funcional e aspectos sociais foram vistos apenas nos pacientes tratados com a estimulação elétrica funcional associada à cinesioterapia. Conclusão:Os dois grupos de pacientes melhoraram com o tratamento, mas a associação da estimulação elétrica funcional à cinesioterapia mostrou superioridade nos subitens capacidade funcional e aspectos sociais da qualidade de vida.